If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 1)(x + -1)(x + -9) = 0 Reorder the terms: (1 + x)(x + -1)(x + -9) = 0 Reorder the terms: (1 + x)(-1 + x)(x + -9) = 0 Reorder the terms: (1 + x)(-1 + x)(-9 + x) = 0 Multiply (1 + x) * (-1 + x) (1(-1 + x) + x(-1 + x))(-9 + x) = 0 ((-1 * 1 + x * 1) + x(-1 + x))(-9 + x) = 0 ((-1 + 1x) + x(-1 + x))(-9 + x) = 0 (-1 + 1x + (-1 * x + x * x))(-9 + x) = 0 (-1 + 1x + (-1x + x2))(-9 + x) = 0 Combine like terms: 1x + -1x = 0 (-1 + 0 + x2)(-9 + x) = 0 (-1 + x2)(-9 + x) = 0 Multiply (-1 + x2) * (-9 + x) (-1(-9 + x) + x2(-9 + x)) = 0 ((-9 * -1 + x * -1) + x2(-9 + x)) = 0 ((9 + -1x) + x2(-9 + x)) = 0 (9 + -1x + (-9 * x2 + x * x2)) = 0 (9 + -1x + (-9x2 + x3)) = 0 (9 + -1x + -9x2 + x3) = 0 Solving 9 + -1x + -9x2 + x3 = 0 Solving for variable 'x'. The solution to this equation could not be determined.
| X-9x=70 | | 2p-9=4p | | 5(15x+20)+9x(30)=78 | | k-14=29 | | 3/5(5x+10)=5/6(12x-18) | | m/11=9 | | 4a+4/5=-4 | | (X-7)+(2x+1)=180 | | 56x^2+53x+12=0 | | 6(k+4)=8k+2 | | w+2=3w+16 | | 3(u-5)-5u=11 | | 7y^2+19y+10= | | x^2+17/9x=25 | | ((3x+6)/(5x^2))((x)/(x^2-4)) | | 7x+(-12/5+2/5)=-8 | | -4x^3+4x^2+3x=0 | | .5x-8=2x+7 | | 0.35x+500=2.5x | | 5y^2-3y-2= | | -5y=-2x+7 | | P(7)=10(7)-7 | | 6+5(3k+4)=146 | | (2x-9)(2x-9)= | | 3+(18-2x(3+4)+1)= | | 5/2x=-40 | | 3a+1b=27 | | 6=10z | | 25.4/275 | | 275/25.4 | | 8.7*1.4= | | ((275/25.4)55)+18 |